Pengaruh Bauran Pemasaran Terhadap Loyalitas Konsumen Kartu Pra Bayar Telkomsel (Studi Kasus Pada Mahasiswa Program Studi Manajemen STIE Pembangunan Indonesia) - Muhlis Muhlis (STIM-LPI Makassar, 2021)
This study aims to determine the effect of the marketing mix on student loyalty in the STIE Pembangunan Indonesia Management Study Program using Telkomsel prepaid cards. Data collection techniques using research instruments in the form of questionnaires. The population in this study were all students of the Management Study Program at STIE Pembangunan Indonesia Economic Studies Program who used Telkomsel prepaid cards. The number of research samples is 77 people, the determination of the sample is by using the Slovin formula. Data analysis used a simple linear regression analysis technique, while a statistical t-test was used to test the research hypothesis. In addition, the coefficient of determination is used to find out how far the proportion of variation of the independent variable can explain the dependent variable well. The results showed: the marketing mix has a significant effect on student loyalty in the STIE Pembangunan Indonesia Management Study Program using Telkomsel prepaid cards. Based on the results of data analysis, it was obtained that the R Square value was 0.364, the effect of the marketing mix on consumer loyalty of students of the STIE Pembangunan Indonesia Management Study Program who used Telkomsel prepaid cards was 36.4%, while the influence of other variables not examined was 63.6%.